Identification and comparison of orthologous argonaute gene sequences in bananas / Pui Han Pin - Pui, Han Pin (2009)
The Argonaute proteins are key components in the effector complex of RNA silencing pathways which interact with small RNAs to mediate sequence specific silencing of nucleic acid targets (reviewed in Carmell et al., 2002; Lingel & Izaurralde, 2004; Cerrutti & Casas-Mollano, 2006; Peters & Meister, 2007; Tolia & Joshua-Tor, 2007; Hutvagner & Simard, 2008). In plants, these proteins are involved in a diversity of biological roles such as antiviral defence, heterochromatin regulation and in the regulation of growth and development (reviewed in Carmell et al., 2002; Ding et al., 2004; Lippman & Martienssen, 2004; Bartel, 2004; Zaratiegui et al., 2007, Vaucheret, 2008, Hutvagner & Simard, 2008). This study represents the first attempt to study the orthologous Argonaute gene sequences in bananas which are an important food staple for many developing nations (Heslop-Harrison & Schwarzacher, 2007; Roux et al., 2008). This study has successfully isolated AGO7-specific PIWI domain genomic sequences from 12 diploid Musa species of three Musa sections and also from Ensete. The Musa AGO7-specific PIWI domain sequences show the highest similarity to rice AGO7/SHOOTLESS4 (average amino acids identity of 78%). Phylogenetic analysis of the Musa sequences revealed phylogenetic grouping that agrees fairly well with the present knowledge of the taxonomic classification of Musa species. In addition, this study estimated that there are about 15 Argonaute genes or loci containing PIWI domain sequences in the genome of Musa acuminata ssp. malaccensis.